Demand-side strategy and business models: Putting value creation for consumers center stage. Issue 1 (February 2018) - Priem, Richard L.; Wenzel, Matthias; Koch, Jochen
Abstract: Value creation for consumers, as the conditio sine qua non for value capture, is at the heart of demand-side strategy research and is a core element of almost any business model. In this paper, we discuss the unique ideas that demand-side strategy and business model research jointly contribute to the strategy literature, and we elaborate on the potential for cross-fertilization between both areas of study. We argue that both the demand-side perspective and the business model concept could jointly promote a better understanding of strategy-making by mutually relying on the distinctive insights from each stream; specifically, while research on demand-side strategy can help business model scholars gain a more robust and granular understanding of effective value propositions, business models can serve as a "bridging concept" that links the shared ideas of both areas of study to resource-based streams of strategy research.